Experimental Study of The Effect of The Animated Film "Wall-E" to Improve Student Listening Skills (Indo-MathEdu Intellectuals Journal, 2023)
Listening is one of the most important parts of communication. Listening is the first skill to learn in English. The animated film "Wall-E" is used for listening learning MTs Al-Ishlah Dasan Agung students to improve English listening skills. The method used in this study is quantitative using a quasi-experimental design. The study used films, field notes and material on "English time" as instruments. The sample in this study was all students of grade VIII MTs Al-Ishlah Dasan Agung from grade 8A to 8B. The instrument used is a test question conducted after watching the animated film "Wall-E". The results showed that the average posttest score of the experimental class was higher than the control class. The use of the animated film "Wall-E" has a significant influence on students' listening skills. In addition, after watching the animated film "Wall-E", the students in the experimental class can improve their listening skills well.